Dynamic analysis of an office building due to vibration from road construction activities - T. Chik, T. N.; Kamil, M. R. H.; Yusoff, N. A.; W. Ibrahim, M. H.
Construction activities are widely known as one of the predominant sources of manmade vibrations that able to create nuisance towards any adjacent building, and this includes the road construction operations. Few studies conclude the construction-induced vibration may be harmful directly and indirectly towards the neighbouring building. This lead to the awareness of study the building vibration response of concrete masonry load bearing system and its vibrational performance towards the road construction activities. This study will simulate multi-storey office building of Sekolah Menengah Kebangsaan (SMK) Bandar Enstek at Negeri Sembilan by using finite element vibration analyses. The excitation of transient loads from ground borne vibrations which triggered by the road construction activities are modelled into the building. The vibration response was recorded during in-situ ambient vibration test by using Laser Doppler Vibrometer (LDV), which specifically performed on four different locations. The finite element simulation process was developed in the commercial FEA software ABAQUS. Then, the experimental data was processed and evaluated in MATLAB ModalV to assess the vibration criteria of the floor in building. The vibration level of floor in building is fall under VC-E curve which was under the maximum permissible level for office building (VC-ISO).